2004
DOI: 10.1158/0008-5472.can-03-1808
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-Derived TNF-Related Apoptosis-Inducing Ligand (TRAIL)

Abstract: To detect the novel genes expressed uniquely in neutrophils and elucidate their function, the gene expression pattern was compared by using cDNA microarray containing 240 cytokine genes between the neutrophils and peripheral blood mononuclear cells (PBMCs) obtained from healthy human donors. Twenty-six genes, including tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), were expressed in neutrophils at a level >10 times higher than that seen in phytohemagglutinin-stimulated PBMCs. The amounts of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
109
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 36 publications
11
109
1
2
Order By: Relevance
“…Consistent with this, blockage of Fas/ FasL function with specific antagonists had no effect on neutrophil spontaneous death [93]. Neutrophils also express other death receptors such as TRAIL-R2 and R3, and their ligand, TNF-related apoptosis-inducing ligand (TRAIL) [98,99]. Neutrophil death can be accelerated by exposure to exogenous TRAIL [98][99][100].…”
Section: Proapoptotic Stimulimentioning
confidence: 88%
See 1 more Smart Citation
“…Consistent with this, blockage of Fas/ FasL function with specific antagonists had no effect on neutrophil spontaneous death [93]. Neutrophils also express other death receptors such as TRAIL-R2 and R3, and their ligand, TNF-related apoptosis-inducing ligand (TRAIL) [98,99]. Neutrophil death can be accelerated by exposure to exogenous TRAIL [98][99][100].…”
Section: Proapoptotic Stimulimentioning
confidence: 88%
“…Neutrophils also express other death receptors such as TRAIL-R2 and R3, and their ligand, TNF-related apoptosis-inducing ligand (TRAIL) [98,99]. Neutrophil death can be accelerated by exposure to exogenous TRAIL [98][99][100]. It has been suggested that TRAIL suppresses certain cytokine-elicited antiapoptotic effects [101,102] and is responsible for neutropenia in systemic lupus erythematosu [103].…”
Section: Proapoptotic Stimulimentioning
confidence: 99%
“…It is noteworthy to point out that molecules other than H 2 O 2 , HOCl and NO· may also mediate the tumoricidal effects of neutrophils. These include proteases [331], membraneperforating agents [331], TNFα [331,332], TRAIL [333] and defensins [334,335].…”
Section: Direct Cytotoxicitymentioning
confidence: 99%
“…Furthermore, Koga et al reported that when Jurkat cells, a well-known leukemic cell line susceptible to TRAIL-mediated killing, were cultured with neutrophils in the presence of IFN-γ, the number of Jurkat cells undergoing apoptosis increased [18].…”
Section: Discussionmentioning
confidence: 99%